2021
DOI: 10.1016/j.csbj.2021.10.024
|View full text |Cite
|
Sign up to set email alerts
|

Conformational selection of vasopressin upon V1a receptor binding

Abstract: Graphical abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 79 publications
0
4
0
Order By: Relevance
“…[49] Hydrodynamic radii were then extracted using the Stokes-Einstein law under the assumption of a spherical diffusion model. [50][51][52] Molecular Dynamics Simulations: Generally, the strategy outlined in Zoltan and Che et al [53][54][55] for simulating non-canonical peptides was followed to generate a starting structure: Structure prediction of the d-and l-blocks using PEPstrMOD, followed by the formation of the iso-peptide bond using the YASARA software package. [56] The resulting structures were then subject to energy minimization and simulated annealing in explicit solvent (atom speed < 2200 m s −1 ; 1% NaCl in water at pH 7.4 and 50 × 10 −3 m sodium phosphate).…”
Section: Methodsmentioning
confidence: 99%
“…[49] Hydrodynamic radii were then extracted using the Stokes-Einstein law under the assumption of a spherical diffusion model. [50][51][52] Molecular Dynamics Simulations: Generally, the strategy outlined in Zoltan and Che et al [53][54][55] for simulating non-canonical peptides was followed to generate a starting structure: Structure prediction of the d-and l-blocks using PEPstrMOD, followed by the formation of the iso-peptide bond using the YASARA software package. [56] The resulting structures were then subject to energy minimization and simulated annealing in explicit solvent (atom speed < 2200 m s −1 ; 1% NaCl in water at pH 7.4 and 50 × 10 −3 m sodium phosphate).…”
Section: Methodsmentioning
confidence: 99%
“…AVP acts through three different vasopressin receptors (78): V 1a , V 1b and V 2 receptors, all of which belong to different isoforms of G protein-coupled receptors (79). A previous study has demonstrated that V 1a is the most abundant and widely distributed vasopressin receptor (80). V 1a -knockout mice show a significant reduction in anxious behavior but also severely impaired social cognition performance (81,82).…”
Section: Mechanism Of Actionmentioning
confidence: 99%
“…Molecular dynamics (MD) simulations that stand on the static crystal structure can predict atomic-level motion and capture the dynamic information of conformational transitions [37] , [38] , [39] , [40] , [41] , [42] , [43] , [44] , [45] , [46] , [47] , [48] , [49] , [50] , [51] , [52] . As a result of computation and algorithmic promotion, MD simulations have become an important source of complementary information in crystallography and a primary tool for mechanism research [53] , [54] , [55] , [56] , [57] , [58] , [59] , [60] , [61] , [62] , [63] , [64] , [65] .…”
Section: Introductionmentioning
confidence: 99%